59 Can heart failure nurse specialists use the surprise question to improve patient access to palliative care services?. (17th July 2020) - McGinlay, Melanie; Straw, Sam; Cowley, Alice; Gierula, John; Paton, Maria; Koshy, Aaron; Drozd, Michael; Cubbon, Richard; Kearney, Mark; Witte, Klaus
Abstract : Introduction: Severe chronic heart failure (CHF) has a high symptom burden due to breathlessness, fatigue and fluid retention, comparable to many types of cancer but despite this, patients are often not referred to palliative care services. The 'Surprise Question' - 'would you be surprised if this patient were to die within the next year?' has been proposed as a screening tool to prompt earlier recognition that patients are nearing the end of life. It forms part of the Gold Standards Framework and is included in the National Institute of Health and Clinical Excellence (NICE) guidance for end-of-life care. We have previously demonstrated the ability of this simple and intuitive question to predict mortality in hospitalised CHF patients and that it can be used by cardiologists and heart failure nurse (HFN) specialists with similar levels of accuracy. Aims: We aimed to determine whether the Surprise Question could influence advanced care planning and referrals to palliative care in hospitalised CHF patients. Methods: Retrospective analysis of 89 hospitalised CHF patients who received either a 'surprised' or 'not surprised' response from their HFN. We analysed the rate of referral to palliative care, completion of not-for-resuscitation status, readmission with decompensation and mortality after 2-years. Results: Sixty patients (67%) received a 'not surprised' and 29 (33%) a 'surprised' response. In patients who received a 'not surprised' response, 25 (28%) were referred to palliative care within the study period, compared to 0 (0%) in the 'surprised' group. The median time from study enrolment to referral was 55 days, which was on average 19 days before death, but occurred within 30-days of enrolment for only 8 patients. Not-for-resuscitation status was completed for 11% and 3% of patients, respectively. The Surprise Question also predicted readmission with decompensation, occurring in 25 (42%) and 4 (14%), and continued to predict mortality beyond 1-year with 35 (58%) and 4 (14%) patients having died respectively. Discussion: Our analysis highlights the potential of the Surprise Question to act as a prompt for earlier referral to palliative care services and advanced care planning. Decompensation of heart failure is a poor prognostic sign, but despite this there was a low rate of not-for-resuscitation decisions during the index admission, and referrals to palliative care were usually made shortly before death. In the future we aim to assess in a randomised controlled trial whether the introduction of the Surprise Question into routine clinical care can achieve these aims. HFNs are able to use the Surprise Question with similar levels of accuracy to cardiologists and are the point of contact for patients with whom they have regular interaction. HFN are therefore ideally placed to develop relationships conducive to palliative care planning and can lead in this area. Conflict of Interest: None